Polyethylene Glycols as Efficient Media for Decarboxylative Nitration of α, β-Unsaturated Aromatic Carboxylic Acids by Ceric Ammonium Nitrate in Acetonitrile Medium: A Kinetic and Mechanistic Study. (4th March 2013) - Ramesh, K.; Shylaja, S.; Rajanna, K. C.; Giridhar Reddy, P.; Saiprakash, P. K.
Abstract : Polyethylene glycols (PEGs) were found to be efficient media for decarboxylative nitration of α, β -unsaturated aromatic carboxylic acids by ceric ammonium nitrate (CAN) in acetonitrile to give β -nitrostyrene derivatives. Kinetics of the reaction exhibited second order kinetics with a first order dependence on [CAN] and [substrate]. Reactions were too sluggish to be studied in the absence of PEG; therefore detailed kinetics were not taken up. Reaction times were reduced from 24 hrs to few hours. The catalytic activity was found to be in the increasing order PEG-300 > PEG-400 > PEG-600 > PEG-200. Mechanism of PEG-mediated reactions was explained by Menger-Portnoy's scheme as applied in micellar kinetics.